2019
DOI: 10.1117/1.jbo.25.3.032005
|View full text |Cite
|
Sign up to set email alerts
|

Submillimeter diameter rotary-pullback fiber-optic endoscope for narrowband red-green-blue reflectance, optical coherence tomography, and autofluorescence in vivo imaging

Abstract: diameter rotary-pullback fiber-optic endoscope for narrowband red-green-blue reflectance, optical coherence tomography, and autofluorescence in vivo imaging,"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Monolithic probe with rotary joint [63] OCT + MSI Model and implementation of depth resolved spectrally sparse color imaging for deep organ structures.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monolithic probe with rotary joint [63] OCT + MSI Model and implementation of depth resolved spectrally sparse color imaging for deep organ structures.…”
Section: Applicationsmentioning
confidence: 99%
“…Either the core or the inner cladding can be used to deliver the fluorescence excitation light, although it was shown that a core delivery allows better fluorescence imaging resolutions [ 77 ]. Additional modalities can be added to such a system including red-blue-green (RGB) reflectance [ 63 ] or spectrally-encoded confocal microscopy (SECM) [ 78 ]. Fluorescence detection can be acquired over a large spectrum for spectroscopic analysis [ 12 ] or target a specific compound by detecting its associated wavelength band.…”
Section: Applicationsmentioning
confidence: 99%
“…This device worked analogously to other OCT devices, except for the difference that the red/green/blue (RGB) light was emitted from the central core, while the collection of the reflected light was performed through the inner cladding. The separation of the various light signals from three modalities was done using an additional WDM [ 50 ].…”
Section: Overview Of Optical Components Used In Endoscopesmentioning
confidence: 99%
“…The new fibre optic and rigid endoscopic techniques have greatly enhanced the diagnostic and dynamic assessment of tumours of the upper aerodigestive tract, particularly the pharynx and larynx [1,2]. The fibre optic endoscope can be further used for optical coherence tomography (OCT) [3,4] and the fiber-optic Raman probe [5] to enhance in-vivo diagnosis of early cancer during endoscopy. A new approach in endoscopic technology today is the electronic endoscope -a medical instrument that can send a front-end device into the human body through a natural entrance of human body or a deliberate surgical incision to observe the tissues and organs in the body [6].…”
Section: Introductionmentioning
confidence: 99%